Interactions between host sex and seasonal changes shape the gut microbial communities of wild blue sheep (Pseudois nayaur) - Dong, Yaxin; Zhang, Zhirong; Zhu, Zhaoling; Hu, Tianhua; Chen, Junda; Teng, Liwei; Liu, Zhensheng (Frontiers in Microbiology, 2025)
The construction of gut microbial communities in wildlife is influenced by both environmental factors and host genetic background. However, the mechanisms through which these factors interact to shape microbial communities remain poorly understood. In this study, we systematically sampled fecal specimens from male and female wild blue sheep across different seasons in Helan Mountain Nature Reserve and analyzed them using 16S rRNA gene sequencing. The objective was to investigate seasonal changes and interactions between sex and season on the gut microbial communities of blue sheep. Our results revealed that Firmicutes and Bacteroidetes were the dominant phyla across all groups, and the ten most abundant genera remain stable across both sexes and seasons. Alpha diversity (Chao1, two-way ANOVA, p = 0.001) and Beta diversity (PCoA, Anosim, R = 0.5410, p = 0.001) analyses further confirmed that seasonal and sex-specific interactions significantly shape the microbial community structure. Notably, the gut microbiomes of male and female blue sheep exhibited distinct response patterns to seasonal changes. LEfSe analysis (LDA > 3) identified 20 microbial taxa with significant seasonal differences, some of which showed sex-specific seasonal variation. These findings highlight the critical role of host sex in modulating the adaptation of gut microbial communities to seasonal environmental stresses. This study provides new insights into the ecological and evolutionary mechanisms of wildlife gut microbiomes and offers a scientific basis for sex-based wildlife conservation strategies.